Decoupling blood telomere length from age in recipients of allogeneic hematopoietic cell transplant in the BMT-CTN 1202 - Lai, Tsung-Po; Verhulst, Simon; Dagnall, Casey L.; Hutchinson, Amy; Spellman, Stephen R.; Howard, Alan; Katki, Hormuzd A.; Levine, John E.; Saber, Wael; Aviv, Abraham; Gadalla, Shahinaz M. (Frontiers in Immunology, 2022)
The age of allogeneic hematopoietic cell transplant (HCT) donors and their hematopoietic cell telomere length (TL) might affect recipients’ outcomes. Our goals were to examine the possible effect of these donors’ factors on the recipients’ hematopoietic cell TL and quantify hematopoietic cell TL shortening in the critical first three-month post-HCT. We measured hematopoietic cell TL parameters in 75 recipient-donor pairs, from the Blood and Marrow Transplant Clinical Trials Network (protocol#1202), by Southern blotting (SB), the Telomeres Shortest Length Assay (TeSLA), and quantitative PCR (qPCR). Recipients’ hematopoietic cell TL parameters post-HCT correlated with donors’ age (p<0.001 for all methods), but not recipients’ own age, and with donors’ pre-HCT hematopoietic cell TL (p<0.0001 for all). Multivariate analyses showed that donors’ hematopoietic cell TL pre-HCT, independent of donors’ age, explained most of the variability in recipients’ hematopoietic cell TL post-HCT (81% for SB, 56% for TeSLA, and 65% for qPCR; p>0.0001 for all). SB and TeSLA detected hematopoietic cell TL shortening in all recipients post-HCT (mean=0.52kb and 0.47kb, respectively; >15-fold the annual TL shortening in adults; p<0.00001 for both), but qPCR detected shortening only in 57.5% of recipients. TeSLA detected a buildup of post-HCT of telomeres <3 kb in 96% of recipients (p<0.0001). In conclusion, HCT decouples hematopoietic cell TL in the recipients from their own age to reflect the donors’ age. The potential donors’ age effect on outcomes of HCT might be partially mediated by short hematopoietic cell TL in older donors. qPCR-based TL measurement is suboptimal for detecting telomere shortening post-HCT.